Genetic Subtype‐Based International Prognostic Index Prognostic Model in Diffuse Large B‐Cell Lymphoma - Lan Mi; Jili Deng; Jiayue Qin; Chen Zhang; Lixia Liu; Shunli Yang; Libin Chen; Hua‐Jun Wu; Haojie Wang; Jun Zhu; Hong Chen; Feng Lou; et al. (MedComm)
ABSTRACT Molecular subtyping in diffuse large B‐cell lymphoma (DLBCL) leads to facilitating drug selection. However, an integrated prognostic model based on molecular subtyping and clinical features has not been well established. Here, we retrospectively performed whole genome sequencing, whole exome sequencing, and fluorescence in situ hybridization in newly diagnosed DLBCLs, established a simplified LymphType algorithm for classification evaluation, and proposed a new integrated prognostic stratification system, combined molecular subtypes and International Prognostic Index (IPI) scoring system in our in‐house sequencing cohort (N = 100), and validated in three public cohorts (N = 1480). Compared with IPI scoring system and classification algorithm model alone, the discrimination ability of prognostic model based on the new integrated model showed best discrimination of overall survival with concordance index value (0.773 vs. 0.724 vs. 0.648). We subsequently established a four‐category risk model defined for the integrated prognostic model as follows: low, low‐intermediate, high‐intermediate, and high risk, demonstrating stronger prognostic separation across all end points (all p < 0.001) in our in‐house cohort and three validation cohorts. Collectively, the new feasible integrated prognostic stratification system contributes to accurate prognosis assessment in clinical routine and provides a new basis for the follow‐up treatment.